Humanisme dalam Serat Jangka Jayabaya Perspektif Javanese Wordview - Sasmita, Gusti Garnis; Joebagio, Hermanu; Sariyatun, Sariyatun (Religió: Jurnal Studi Agama-agama, 2018)
Serat Jangka Jayabaya is a literary work that can be used as a source of historical learning. The local genius of Javanese worldview is reflected in humanism values in the manuscript. Which is much misunderstood by most people even historians. This study uses qualitative research methods that reveal the value of Jayabaya humanism based on content, authorship and axiological manuscripts through interviews and literature studies. The results show that the concept of "jangka" is the guidance as well as the control of Java society in viewing various social phenomena. The guidelines are summarized in the concept of humanism values reflected as knowledge, equity, equality, dignity, and moral ethics.